An appraisal of section 377A and section 377B of the penal code (act 574) / Samir Zainal Zainal, Rezli Endi Ramli and Roslizi Sulaiman - Zainal, Samir Zainal; Ramli, Rezli Endi; Sulaiman, Roslizi (2007)
Our objective is to appraise Section 377A and 377B of Malaysian Penal Code by looking into the essence of the law itself as to its effectiveness and its relevance to the Malaysian society. Will it help moralize society or just enforce it on them? The scope of this research will be on the applicability and the practicality of those sections in Malaysia and whether they are suitable towards the globalize world or in need of further revising to suite the evolution of the Malaysian society. This research will be based on books, articles, magazines, journals and other suitable materials from the law library of Mara University of Technology, Malaysia (PTAR UiTM Malaysia). Furthermore, observation also is made to the culture and acceptance of the particular involved in our research through the forum section in then internet and individual's life.